The mediating influence of music festival experience in the relationship between event quality, perceived value, and revisit intentions of gen z consumers on Metro Manila - Mary Jean Lopez; Jasmine Loberanes; Glenn Gerard Agoo; Ma.Cristina Q. Trinidad (Journal of Rural Tourism, 2026)
Purpose – This study aims to examine the mediating role of Music Festival Experience in the relationships between event quality, perceived value, and revisit intentions among Generation Z consumers in Metro Manila.Design/Methodology/Approach – A quantitative approach was employed using a structured survey targeting Gen Z attendees aged 18 to 27. Data were analysed through regression and mediation analyses to explore the relationships among event quality, perceived value, music festival experience, and revisit intentions.Findings – The results indicate that event quality significantly influences perceived value, which in turn positively affects revisit intentions. Furthermore, Music Festival Experience serves as a key mediating variable, strengthening the relationship between perceived value and revisit intentions. These findings highlight the importance of delivering high-quality and engaging festival experiences to enhance attendee satisfaction and encourage repeat participation.Originality/Value – This study contributes to event and tourism literature by emphasizing the mediating role of experiential factors in shaping behavioural intentions among younger audiences. It provides practical insights for event organizers and marketers to design immersive and value-driven festival experiences, while also suggesting avenues for future research, including comparative studies across generations, the role of sponsorship and sustainability, and the use of qualitative approaches to capture deeper emotional engagement.